M Theory Compactified On G2 Manifold With Background Fluxes - Freddy P. Zen; Bobby E. Gunara; Arianto Arianto (Institut Teknologi Bandung, 2005)
Some geometrical aspects of M-theory compactified on seven dimensional G2 manifold with background fluxes are considered. It turns out that this model admits N=1 supersymmetry. We also discuss the arising holomorphic superpotential and the scalar potential with its possible vacua.